SAT0606 RISK OF MAJOR AUTOIMMUNE DISEASES IN PATIENTS WITH FEMALE BREAST CANCER: A NATIONWIDE, POPULATION-BASED COHORT STUDY. (June 2019) - Chen, Hsin-Hua; Chen, Chien-Chih; Lin, Ching-Heng; Chen, Der-Yuan; Chao, Wen-Cheng
Abstract : Background: Prior studies showed that breast cancer patients had an increased spontaneous expression of CTLA-4 on T lymphocytes in breast tissue and peripheral blood mononuclear cells, leading to impaired T cell activation. We hypothesized that breast cancer patients may have a decreased risk of autoimmune diseases. However, the incidences of autoimmune disease in breast cancer are still unclear. Objectives: To investigate the risk of major autoimmune diseases including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), Sjögren's syndrome (SS), polymyositis (PM)/dermatomyositis (DM) in female breast cancer patients. Methods: We identified all newly-diagnosed female breast cancer patients during 2007–2013 using the 1997–2013 Taiwanese national health insurance database as the incident female breast cancer cohort. We randomly selected non-breast cancer female controls matching female breast cancers patients for age and the year of index date from one million representative population as the comparison cohort. We estimated the risks of SLE, RA, SS and PM/DM in female breast cancer patients compared with the comparison cohort using Cox regression analysis adjusting for age, Charlson comorbidity index, hormone therapy and chemotherapy. Results: A total of 54, 311 female breast cancer patients and 217, 244 matched non-breast cancer female individuals were included. The mean ± SD age was 53.6±12.7 years in both groups. After adjusting for potential confounders, female breast cancer patient had a lower risk of developing SLE (hazard ratio [HR], 0.04; 95% confidence interval [CI], 0.01–0.24), RA (HR, 0.03; 95% CI, 0.02–0.04) and SS (HR, 0.21; 95% CI, 0.09–0.48) than the comparison cohort. However, the risk of PM/DM was not significantly different between female breast cancer group and the comparison group (HR, 0.37; 95% CI, 0.08–1.80). SS: Sjogren's Syndrome; RA: Rheumatoid Arthritis; SLE: Systemic Lupus Erythematosus. # Using Cox proportional hazard regression model *Adjusted variables included age, Charlson comorbidity index, hormone therapy and chemotherapy. Female breast cancer patients had a decreased risk of developing SLE, RA and SS, but not PM/DM. Conclusion: Female breast cancer patients had a decreased risk of developing SLE, RA and SS, but not PM/DM. References: [1] Mao H, Zhang L, Yang Y, Zuo W, Bi Y, Gao W, et al. New insights of CTLA-4 into its biological function in breast cancer. Curr Cancer Drug Targets. 2010;10:728-36. [2] Khalife E, Khodadadi A, Talaeizadeh A, Rahimian L, Nemati M, Jafarzadeh A. Overexpression of Regulatory T Cell-Related Markers (FOXP3, CTLA-4 and GITR) by Peripheral Blood Mononuclear Cells from Patients with Breast Cancer. Asian Pac J Cancer Prev. 2018;19:3019-25. Disclosure of Interests: Hsin-Hua Chen Speakers bureau: Johnson & Johnson, Novartis, Pfizer, Abbvie, Roche, UCB, Bristol-Myers Squibb, Chugai, Chien-Chih Chen: None declared, Ching-Heng Lin: None declared, Der-Yuan Chen: None declared, Wen-Cheng Chao: None declared